Early-onset pancreatic neuroendocrine neoplasms: A distinct disease with improved survival compared with old individuals - Yang, Zhen; Liu, Caiyun; Leng, Kaiming; Liu, Lianshuang; Shi, Guangjun (Frontiers in Endocrinology, 2023)
Abstract Background: The incidence, clinicopathologic characteristics, treatment patterns, and survival of early-onset pancreatic neuroendocrine neoplasms (EOPanNENs) have not been well explored. Methods: Patients diagnosed with PanNENs were identified from the SEER database between 2000 and 2018. EOPanNENs were defined as diagnosis in patients aged less than 50 years, while the remaining were defined as later-onset pancreatic neuroendocrine neoplasms (LOPanNENs). Incidence, clinical features, management, and prognosis were analyzed in our study. Multivariable analyses were performed to identify factors associated with overall survival (OS) in EOPanNENs and LOPanNENs, respectively. Results: A total of 5172 patients with PanNENs were included: 1267 (24.5%) in the EOPanNENs cohort and 3905 (75.5%) in the LOPanNENs cohort. The age-adjusted incidence rate significantly increased among late-onset cases, while it remained relatively stable in early-onset cases. EOPanNENs were more frequently to be female, unmarried, and with better tumor differentiation compared with LOPanNENs. Of note, early-onset patients presented with a higher rate of lymph node involvement, and they were more likely to receive surgical treatment. For local-regional disease at presentation, surgery alone was the most frequently used regimen over the last two decades. With regard to distant stage, a combination of surgery and chemotherapy was more often utilized. Risk factors for PanNENs survival were more correlated with LOPanNENs compared with EOPanNENs. The OS and cancer-specific survival (CSS) were significantly better in the EOPanNENs group. Further analyses showed that EOPanNENs≤2cm were associated with more favorable survival outcomes than EOPanNENs>2cm. Conclusion: EOPanNENs are a clinically rare and distinct entity from LOPanNENs. The advantages in survival for the EOPanNENs cohort over time were largely driven by the indolent clinical courses including better tumor differentiation and intensified surgical treatment. Further investigations are warranted to better understand the characteristics of this disease subgroup.